CULTURALL HERITAGE INFORMATION SYSTEM (SIGAYA) IN KERAMAS VILLAGE USING EXTREME PROGRAMMING METHOD - Jayantara, Putu Agus Raditya; Wijaya, I Nyoman Yudi Anggara; Putra, I Gede Juliana Eka (Institut Bakti Nusantara, 2023)
Keramas Village is part of the Blahbatuh District, Gianyar Regency, Bali Province, with an area of 72 hectares. Keramas Village is one of the tourist villages in Gianyar Regency which is located on the 4 km long coast. One of the villages currently developing village potential-based tourism is Keramas Village. Keramas Village has a historical side that is still preserved. One of them is evidenced by the still sturdy existence of the statues which are housed in Besakih Temple and Kebo Edan Temple which have been designated as ancient sites. The head of the Keramas Tourism Awareness Group (Pokdarwis) Mrs. Eka Sri Wedayanti when interviewed said that the culturall heritage in Keramas village has not been optimally developed so far. this is because historical information regarding the existence of the culturall heritage is not generally known by the public or tourists visiting Keramas Village. This research will discuss the design and construction of a website-based culturall heritage preservation information system (SIGAYA) using the extreme programming method. It is hoped that this research can help convey information so that it can be more easily accessed by the public and tourists, thus making it easier for Pokdarwis to manage culturall heritage data and its potential.